Central flow tilting disc valve for aortic valve replacement - Björk, Viking Olov (1970)
A new central flow tilting disc valve has been introduced. The clinical experience from the first 50 patients treated with aortic valve replacement and followed up for 12 months is reported. The results obtained are so encouraging that the tilting disc valve is at present preferred for all aortic valve replacements in this institution.